2013
DOI: 10.1103/physrevb.88.155105
|View full text |Cite
|
Sign up to set email alerts
|

Cluster expansion made easy with Bayesian compressive sensing

Abstract: Long-standing challenges in cluster expansion (CE) construction include choosing how to truncate the expansion and which crystal structures to use for training. Compressive sensing (CS), which is emerging as a powerful tool for model construction in physics, provides a mathematically rigorous framework for addressing these challenges. A recently-developed Bayesian implementation of CS (BCS) provides a parameterless framework, a vast speed up over current CE construction techniques, and error estimates on model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 53 publications
0
81
0
Order By: Relevance
“…A combination of DFT calculation and the cluster expansion (CE) method [14][15][16] is also useful for alloys. Recent progress in combining the CE method with DFT calculations [17][18][19][20][21][22][23][24][25][26][27][28] has enabled us to evaluate the ground-state structures and phase stability accurately. Although it is impossible to find structures beyond a given crystal lattice using the ordinary CE method, many yet-unobserved structures have been discovered within alloy configurations on the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of DFT calculation and the cluster expansion (CE) method [14][15][16] is also useful for alloys. Recent progress in combining the CE method with DFT calculations [17][18][19][20][21][22][23][24][25][26][27][28] has enabled us to evaluate the ground-state structures and phase stability accurately. Although it is impossible to find structures beyond a given crystal lattice using the ordinary CE method, many yet-unobserved structures have been discovered within alloy configurations on the crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that a similar problem in alloy theory, the cluster expansion (CE) method for configurational energetics [21,22], can be solved efficiently and accurately using compressive sensing [23,24]. CS has revolutionized information science by providing a mathematically rigorous recipe for reconstructing S-sparse models (i.e., models with S nonzero coefficients out of a large pool of possibles, N , when S N ) from a set of only O(S) data points [25][26][27].…”
mentioning
confidence: 99%
“…(4). For the discrete orthogonal basis in the CS cluster expansion [23,24], i.i.d. sensing matrices A could be obtained by enumerating all ordered structures up to a certain size and choosing those with correlations that map most closely onto quasi-random vectors.…”
mentioning
confidence: 99%
“…The ''best'' model for the alloy system is obtained by minimizing the cross-validation score S CV , in the spirit of model-selection approaches. Several innovative algorithms have been developed for this purpose [14][15][16][17][18][19]22,23] techniques. Among these, the GA-based algorithm, which performs unbiased search, is noteworthy since the resultant cluster set a does not obey the hierarchical and compactness conditions.…”
Section: Framework and Implementation Of The Dft + Cemc Approachmentioning
confidence: 99%
“…In earlier implementation of DFT + CEMC, the set {a} were intuitively selected or progressively expanded to improve predictability. In recent years, methods from the field of regression analysis, machine learning and signal processing, which includes genetic algorithm (GA) [14], variational method [15], Bayessian approach [16,17], and compressive sensing algorithm [18,19], have been applied to the problem of finding {a} leading to highly accurate cluster expansion (CE). These algorithms are based on general strategy to minimize the cross-validation score S CV which represent the error between CE predicted energy and DFT energy not used in the training set.…”
Section: Introductionmentioning
confidence: 99%